Review of Laser Therapy in Cardiovascular Diseases: Laser in cardiovascular diseases - Karvandi, Mersedeh (Journal of Lasers in Medical Sciences, 2021)
Introduction: In recent years, there has been a rise in laser therapy for the treatment of cardiovascular diseases. Methods: This paper attempted to represent recent advances in laser therapy in cardiovascular tissue repairs. Three standard techniques have been explicitly described herein cardiovascular tissue repairs by laser. Results: One of the advantages of using laser therapy in cardiovascular diseases is its non-invasiveness. It also reduces the treatment process pain and prevents massive surgical incisions and bleeding throughout the operation. Laser therapy can ensure an alternative method to treat the ischemic region of the heart and creating anastomosis of vessels. Conclusion: With professional technologies and endoscopic surgery method development, the role of using lasers has become much more precise and more transparent in cardiovascular diseases. DOI: 10.34172/jlms.2021.52.